2017
DOI: 10.1021/acsami.7b14208
|View full text |Cite
|
Sign up to set email alerts
|

Core Levels, Band Alignments, and Valence-Band States in CuSbS2 for Solar Cell Applications

Abstract: The earth-abundant material CuSbS (CAS) has shown good optical properties as a photovoltaic solar absorber material, but has seen relatively poor solar cell performance. To investigate the reason for this anomaly, the core levels of the constituent elements, surface contaminants, ionization potential, and valence-band spectra are studied by X-ray photoemission spectroscopy. The ionization potential and electron affinity for this material (4.98 and 3.43 eV) are lower than those for other common absorbers, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 97 publications
(257 reference statements)
4
52
0
Order By: Relevance
“…This indicates the intensified carrier scattering due to factors other than carrier interactions, which could be related with the decreasing fraction of c-CTS that has a higher σ than t-CTS [35]. Accordingly, the S values are enhanced as a result of the reduced n due to Sb doping, from ~54 μV K -1 for the x = 0 sample at 323 K to ~84 μV K -1 for the x = 0.08 one (see Figure 6 Actually, a similar effect has been clarified in CuSbS 2 [39], which would cause a net increase of density-of-states (DOS) near the Fermi level when the lone pair electrons first interact with S 3p electrons and the full antibonding orbital of this interaction is then sufficiently high so that it can subsequently interact with empty Sb 5p states, resulting in bonding states in the valence band and antibonding states at the bottom of the conduction band.…”
Section: Resultsmentioning
confidence: 53%
“…This indicates the intensified carrier scattering due to factors other than carrier interactions, which could be related with the decreasing fraction of c-CTS that has a higher σ than t-CTS [35]. Accordingly, the S values are enhanced as a result of the reduced n due to Sb doping, from ~54 μV K -1 for the x = 0 sample at 323 K to ~84 μV K -1 for the x = 0.08 one (see Figure 6 Actually, a similar effect has been clarified in CuSbS 2 [39], which would cause a net increase of density-of-states (DOS) near the Fermi level when the lone pair electrons first interact with S 3p electrons and the full antibonding orbital of this interaction is then sufficiently high so that it can subsequently interact with empty Sb 5p states, resulting in bonding states in the valence band and antibonding states at the bottom of the conduction band.…”
Section: Resultsmentioning
confidence: 53%
“…11 The bandgap obtained for CAS 20, 30 and 40 lms are 1.63, 1.58, 1.50 eV respectively. 43 The widest bandgap observed for 20 nm CAS lm might be due to the higher extent of unreacted Sb 2 S 3 present in it. Sanchez et al reported that the higher electron-hole pair generation and potent absorption coefficient resulted due to the direct band gap 44 which is suitable for the optoelectronic device applications.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…On the other hand, the device structure of CuSbS 2 is directly inherited from CIGS counterpart. More study on the band alignment and interface defects of such heterojunction needs to be conducted . It is reported that CuSbS 2 and CdS could form a slight “cliff‐like” conduction band offset (CBO) by ultraviolet photoelectron spectroscopy analysis or even severe 0.85 eV “cliff‐like” CBO by X‐ray photoelectron spectroscopy characterization, neither of which falls within the favourable region of 0 to 0.4 eV “spike‐like” CBO and thereby causing large V oc deficit (E g /q – V oc ).…”
Section: Introductionmentioning
confidence: 99%